The hydrocarbon generation potential of the mudstone source rock in the Jurassic Shuixigou Group, the Turpan-Hami Basin, and indicative significance for oil and gas exploration - Tong Lin; Kangle Wang; Haidong Wang; Runze Yang; Pan Li; Long Su (Natural Gas Industry B)
The coal-bearing source rocks in the Jurassic Shuixigou Group have received widespread attention as the primary source rocks in the Turpan-Hami Basin of China, but the hydrocarbon generation potential and process of the mudstone in the Shuixigou Group, especially the mudstone at the top of the Sangonghe Formation, are unclear. Taking the source rocks of the Xishanyao Formation and the Sangonghe Formation as objectives, this study conducted rock pyrolysis and gold tube simulation experiment to investigate their hydrocarbon generation characteristics and differences. Our results indicate that the source rocks of the Xishanyao Formation include mudstone, carbonaceous mudstone and coal, and the quality of the source rocks is highly heterogeneous; the source rocks of the Sangonghe Formation are mainly composed of mudstone, and it is a good gas source rock. Simulation experiments found that the activation energy required for the generation of gaseous hydrocarbons by the mudstone of the Sangonghe Formation is lower than that by the mudstone of the Xishanyao Formation. The hydrocarbon generation process can be divided into three stages for both formations, but the gas generation potential of the Xishanyao Formation mudstone is higher than that of the Sangonghe Formation mudstone. A large amount of hydrocarbon was generated by the mudstone of the Xishanyao Formation when entering late thermal evolution, of which methane is dominant, mainly from the demethylation reaction of mature kerogen. On the other hand, a large amount of hydrocarbon was generated by the mudstone of the Sangonghe Formation in the early stage of thermal evolution, of which light hydrocarbon and wet gas are dominant, mainly from the early cracking stage of kerogen. This difference may be attributed to the structure of kerogen. The mudstone of the Xishanyao Formation is conducive to the formation of highly mature dry gas reservoirs, while the mudstone of the Sangonghe Formation is conducive to the formation of low maturity condensate gas and volatile oil reservoirs. The research result provides a scientific basis for the comparison of oil and gas sources and the evaluation of oil and gas resources in the Turpan-Hami Basin.